Safely Implementing the Direct Anterior Total Hip Arthroplasty: A Methodological Approach to Minimizing the Learning Curve. Issue 22 (15th November 2020) - Pirruccio, Kevin; Evangelista, Perry J.; Haw, Jonathan; Goldberg, Tyler; Sheth, Neil P.
Abstract : Introduction: Orthopaedic surgeons often cite concern for a learning curve as a barrier to adopting the direct anterior approach (DAA) for total hip arthroplasty (THA) while transitioning from other approaches. Studies both assessing and describing a practical approach and strategy to safely accomplish this transition, as well as the effect on clinical outcomes, are not well described. Methods: This prospective study compares a single surgeon's operative results and complications for the first consecutive 100 direct anterior THA to the last 100 consecutive posterior THA after 7 years in practice. The regimented and disciplined learning strategy used to implement the DAA is detailed in this study. The data were analyzed using univariate and multivariate regression models. Results: Univariate analyses identified significant differences in sex, age, Asian race, and diagnostic cause for THA between the two cohorts. Multivariate analyses controlled for these differences and showed that relative to posterior THA, direct anterior THA cases were associated with 7-minute longer procedures ( P = 0.002) and lengths of stay that were 0.7 days fewer ( P = 0.013). No significant differences were present in the estimated blood loss, and importantly, no significant differences in death or surgical complication rates between cohorts. Discussion: This study suggests that the DAA for THA can be safely implemented without the increased and adverse risk to the patient when a structured learning process is maintained and meticulously performed.